Multi-disciplinary trends in artificial intelligence : 9th International Workshop, MIWAI 2015, Fuzhou, China, November 13-15, 2015 : proceedings /: 9th International Workshop, MIWAI 2015, Fuzhou, China, November 13-15, 2015 : proceedings. (2015) - Unknown
No abstract available